Clinical usefulness of dental X-ray computed tomography for postoperative assessment of secondary alveolar bone grafting - NOGUCHI, Kazuhide; SONOYAMA, Tomoo; SETO, Kanichi; ISHII, Hiroaki; KAWARADA, Takashi; IINO, Mitsuyoshi; HAMADA, Yoshiki; NIITSU, Kouta; KONDOH, Toshirou (Japanese Journal of Oral and Maxillofacial Surgery, 2003)
In this study, the clinical usefulness of dental X-ray computed tomography (CT) for postoperative assessment of secondary alveolar bone grafting was investigated. Nineteen bone-grafted alveolar clefts in 15 patients with cleft lip and palate were studied. All bone bridges were examined by dental three-dimensional (3D)-CT (PSR 9000: Asahi Roentgen, Kyoto, Japan). The postoperative three-dimensional morphology of the bone bridges was easily recognized. Dental 3 DCT images were suggested to be useful for assessment before installation of dental implants in bone bridges. In addition, the status of bone surrounding the installed dental implants and the periodontal space of teeth adjacent to the cleft could be clearly evaluated. In conclusion, Dental 3 D-CT provides clinically valuable information for the postoperative assessment of secondary alveolar bone grafting.